The Techno-Economic Benefit of Sorption Enhancement: Evaluation of Sorption-Enhanced Dimethyl Ether Synthesis for CO2 Utilization - Skorikova, Galina; Saric, Marija; Sluijter, Soraya Nicole; van Kampen, Jasper; Sánchez-Martínez, Carlos; Boon, Jurriaan (Frontiers in Chemical Engineering, 2020)
Dimethyl ether (DME) is an important platform chemical and fuel, that can be synthesised from CO2 and H2 directly. In particular, sorption-enhanced DME synthesis (SEDMES) uses the in situ removal of H2O with an adsorbent to ensure a high conversion efficiency in a single unit operation. The in situ removal of steam has been shown to enhance catalyst lifetime and boost process efficiency. In addition, the hydrogen may be supplied through water electrolysis using renewable energy, making it a promising example of (indirect) Power-to-X technology (PtX). Recently, major advances have been made in SEDMES, both experimentally and in terms of modelling and cycle design. The current work presents a techno-economic evaluation of SEDMES using H2 produced by a PEM electrolyser. A conceptual process design has been made for the conversion of CO2 and green H2 to DME, including the purification section to meet ISO fuel standards. By means of a previously developed dynamic cycle model for the SEDMES reactors, a DME yield per pass of 72.4 % and a carbon selectivity of 84.7 % were achieved for the studied process design after optimization of the recycles streams. The production costs for DME by the PtX SEDMES process at 23 kt/year scale, are determined at ~€1.3 per kg. These costs are higher than the current market price, but lower than the cost of conventional DME synthesis from CO2. Factors with the highest impact on the business cases are the electricity and CO2 cost price as well as the CAPEX of the electrolyser, which is considered an important component for technology development. Furthermore, as the H2 cost constitute the largest part of the DME production cost, SEDMES is demonstrated to be a powerful technology for efficient conversion of green H2 into DME.